Application of polyhedral mesh for vortex formation study for simple single pump sump - Samsudin M.L.; Hasini H. (Penerbit Akademia Baru, 2023)
Meshing of domain in CFD is an important step to ensure accuracy of the solution. In the past, hexahedral or tetrahedral mesh systems were commonly used, and both have their merits and demerits. For large and complex geometry, polyhedral is another option but its accuracy is claimed to be lacking. In this paper, the use of polyhedral mesh system by past researchers are reviewed. Evaluation on the application of polyhedral mesh system for the study of the vortex formation with a simple single pump sump model is made. Validation was made through the comparison of the results from hexahedral, tetrahedral and polyhedral mesh sizes and the experimental data from published data. The polyhedral mesh system was found to perform satisfactorily and was able to match the results from the hexahedral mesh system as well as the experimental data. 2021, Penerbit Akademia Baru. All rights reserved.